PEMBELAJARAN BAHASA INGGRIS DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI SEKOLAH MENENGAH ATAS NEGERI 2 KOTA MADIUN - Budi Santoso, Agus; Sumani, Sumani (Jurnal Pendidikan, 2008)
This research serves a thorough discussion on: 1) the implementation of Contextual Teaching and Learning for English subject; 2) the implementation of evaluation under Contextual Teaching and Learning for English subject.This research is conducted at SMA Negeri 2 Madiun Municipality by the descriptive-qualitative method under naturalistic research design. The source of data are: 1) events, 2) informers, and, 3) files. The strategies of accumulating-the data are observation, in- depth interview and documents investigation. Clipping technique used in this research is the criterion-based selection. Source triangulation is used to guarantee the data validity. The data analysis is carried out by the use of Miles and Hubermans interactive analysis.The analysis results in conclusions that: the implementation, of contextual teaching and learning includes three steps, i.e. planning, implementing and evaluating. In the planning stage, the teachers get the lesson plans from the teachers association so as to get the uniformity in format for all of English teachers in Madiun Municipality. The standardization of lesson plan format throughout Madiun Municipality is against the principles of contextual teaching and learning. In the implementation stage, it is shown that teachers do not completely implement the principle of contextual teaching an learning due to the lack of teachers knowledge in contextual teaching and learning principles. The authentic assessment suggested by the contextual teaching and learning can not either be implemented satisfactorily by the teachers. Two out of other reasons are: that firstly, authentic assessment is regarded difficult to carry out because of the lack of facilities for this. Secondly, the teachers are mostly discouraged by the inaction of standardized national test, which is believed of confronting the essence of contextual teaching and learning evaluation system. They are so determined if the learning and teaching process are mainly supposed to make the students get the high scores in the standardized national test that they forget the principles of contextual teaching and learning.Key terms: English learning, Contextual teaching and learning